Online health information seeking behavior of non-communicable disease (NCD) among government employees in Putrajaya Malaysia - Mazlan, Azriey; Adzharuddin, Nor Azura; Omar, Siti Zobidah; Tamam, Ezhar (UKM Press, 2021)
Seeking health information is becoming more convenient with various health resources online. It would be beneficial to explore the perception of individuals’ health status concerning health information seeking and eHealth literacy. With government employees in Putrajaya found to be at high risk of Non-Communicable Disease (NCD), based on the high rate of obesity, it is beneficial to explore the factors associated with OHISB among this population to ensure adequate attainment and sharing of health information and self-management resources. The Comprehensive Model of Information Seeking (CMIS) is used to measure the factors that influence online health information-seeking behaviour (OHISB). Based on previous studies, the CMIS is commonly used to examine cancer patient’s information seeking on health information behaviour. However, this paper will be focusing on government employee’s behaviour in using online information as to their health reference. Previous studies have shown that information seeking has resulted in changes in the behaviour of cancer patients. It is believed that the outcome of this study will be beneficial in terms of developing strategies to encourage a healthier lifestyle among this population to prevent the occurrence of NCDs. Therefore, this paper elaborates on some of the theories used in previous studies to enrich individual and community online health information-seeking behaviour and health knowledge dissemination. The findings of this study show the direct relationships between trust in internet health and eHealth Literacy were significant towards OHISB. However, the direct relationships between direct experience, salience, unmet information needs and self-efficacy belief towards OHISB were not significant.